Pro expression blend 4 - Troelsen, Andrew (Apress, 2011)
Pro Expression Blend 4 is for .NET developers and graphical artists who want to learn the ins and outs of the Expression Blend integrated development environment. You may know already that this tool can be used to build Windows Presentation Foundation (WPF), Silverlight, and Windows Phone 7 applications; however, this book will take you well beyond the basics and provide you with a detailed examination of key Blend topics, including workspace customization, graphics, layout, styles, themes, data binding, and the use of SketchFlow, giving you an excellent understanding of the Blend product and what it can do for you. Over the course of these eight chapters, you will learn numerous techniques to simplify the authoring of XAML using Blend. These include: Transforming a vector graphic into a custom control template with a few clicks of the mouse Generating complex animations using an integrated timeline editor Visually designing interactive data templates Creating prototypes (via SketchFlow) that can be transformed into production-level code Throughout Pro Expression Blend 4, you'll work with both Blend and .NET code to finalize fully-functional projects that will provide both valuable insights and a sound foundation for your future WPF and Silverlight projects. Each chapter will give you ample opportunity to build .NET software using Blend. However, this is not a programming book, per se. While some examples will require a manageable amount of C# code, this book is squarely focused on helping you gain mastery over the numerous tools, editors, designers, and wizards of the Microsoft Expression Blend IDE.